2015
DOI: 10.1136/annrheumdis-2015-eular.5279
|View full text |Cite
|
Sign up to set email alerts
|

OP0163 Treatment-Naïve, Early Rheumatoid Arthritis Patients Demonstrate Vascular and Myocardial Abnormalities on Cardiac MRI

Abstract: BackgroundCardiac studies of patients with rheumatoid arthritis (RA) have demonstrated abnormalities in left ventricular (LV) remodelling that is associated with development of heart failure and cardiovascular (CV) morbidity and mortality1,2. No studies to date have evaluated for changes in myocardial and vascular function in treatment-naïve early RA (ERA).ObjectivesTo evaluate whether patients with newly diagnosed, treatment-naïve ERA demonstrate myocardial and vascular changes on cardiac MRI (CMR) compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Overall, modest event rate has necessitated the use of surrogate CV abnormalities of increased CV risk including arterial stiffness. Increased arterial stiffness is well recognised in established RA,2 with early, similar reports using comprehensive and reliable cardiac MRI (CMRI) in our treatment-naïve, early onset RA cohort 3. Autopsy, histopathological and clinical studies in general population and RA cohorts with and without CV disease (CVD) suggest citrullinated proteins as a mechanism for atherosclerosis, including presence of citrullination within the atherosclerotic plaque of subjects without RA 4 5.…”
supporting
confidence: 74%
“…Overall, modest event rate has necessitated the use of surrogate CV abnormalities of increased CV risk including arterial stiffness. Increased arterial stiffness is well recognised in established RA,2 with early, similar reports using comprehensive and reliable cardiac MRI (CMRI) in our treatment-naïve, early onset RA cohort 3. Autopsy, histopathological and clinical studies in general population and RA cohorts with and without CV disease (CVD) suggest citrullinated proteins as a mechanism for atherosclerosis, including presence of citrullination within the atherosclerotic plaque of subjects without RA 4 5.…”
supporting
confidence: 74%
“…Although Ntusi et al reported similar LVEF, they did determine reduced peak systolic circumferential strain and reduced diastolic strain rate in those with RA [8]. Similarly, smaller CMR studies have not described reduced LV mass [8,12], although our research group has reported preliminary findings of lower LV mass, in treatment-naive early RA patients (n = 66) [10]. Echocardiography studies have repeatedly reported increased LV mass in patients with RA [32], and often no difference in LVEF [11,33], although reduced LVEF has been associated with active disease [33].…”
Section: Discussionmentioning
confidence: 52%
“…The largest CMR study in RA (n = 75, some with diabetes) reported a 4.4% reduction in LV ejection fraction (LVEF), but interestingly also a 15% reduction in LV mass index (LVMI) in those with RA [9]. A preliminary CMR report of 66 patients with treatment-naive early RA also demonstrated a reduced LVMI [10]. Both of these CMR studies stand in contrast to echocardiographic data [11] and smaller CMR studies in RA [8,12] reporting no difference or increase in LV mass.…”
Section: Introductionmentioning
confidence: 99%
“…These data were partly presented at the American College of Rheumatology meeting. 28 Early rheumatoid arthritis cohort: baseline to 1 year…”
Section: Patients Compared With Control Subjectsmentioning
confidence: 99%